The Impact of the Pandemic on Digital Literacy Skills for Online Teaching in Zimbabwean Schools: A Mixed-Methods Research Approach - Magocha, Medicine; Munyaradzi, Juliet; Babalola, Sunday Samson (Research in Social Sciences and Technology, 2025)
The COVID-19 pandemic has forced a rapid shift to online teaching and learning, presenting challenges for teachers in developing countries such as Zimbabwe. This study employed a sequential mixed-methods research approach to explore how rural Zimbabwean teachers relate to digital technologies and how their digital literacy skills impacted their online teaching during the pandemic. An online questionnaire was administered to a purposeful sample of 100 teachers, followed by telephone interviews with ten key informants selected through cluster sampling. The findings revealed that limited digital literacy skills and socioeconomic factors were major barriers for rural secondary school teachers in accessing, creating, evaluating, and sharing teaching information with their learners. This study highlights the need for increased support to enhance teachers' technological knowledge in the face of complex demands for digital literacy, exacerbated by unprecedented challenges such as worldwide pandemics. The mixed-methods research approach allowed for a comprehensive investigation of this complex educational problem, drawing on qualitative and quantitative perspectives to capture the historical context and multifaceted nature of teachers' challenges in integrating digital technologies into their teaching practices.